Increasing Social Skills Competencies to Prepare for Careers of Children with Special Needs - Daroni, Gangsar Ali; Gunarhadi, Gunarhadi; Legowo, Edy (Indonesian Journal of Disability Studies, 2018)
This study aims to determine the efforts of extraordinary schools in improving social skills competence as an effort to prepare for careers of children with special needs. This study uses descriptive qualitative research methods. This research was conducted at SLB N Sukoharjo, SLB N Surakarta and SLB N Colomadu. Subjects in this study were six teachers and three principals in the Special School which were used as research sites. Research data were collected through interviews, observation, and documentation. The analysis technique in this study uses descriptive analysis. The results showed that efforts to improve social skills competencies to prepare for careers of children with special needs in extraordinary schools were carried out through the learning of social science. The social skill material taught is adapted to the child's ability. Barriers that occur in efforts to improve social skills are lack of parental support and a less inclusive social environment. The solution, schools can socialize with parents to teach social skills at home and socialization to the community environment to become an inclusive society.